2017
DOI: 10.1159/000477604
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Injury Increases the Expression of Alpha-2/Delta-1 Subunit of L-Type Calcium Channel in Sensory Neurons of Rat Spinal and Trigeminal Nerves

Abstract: By immunohistochemistry, an effect of nerve injury on distribution of alpha-2/delta-1 subunit of L-type calcium channel was investigated in rat's 4th and 5th lumbar dorsal root ganglia (DRGs), trigeminal ganglion (TG), and mesencephalic trigeminal nucleus (Mes5). The immunoreactivity was expressed by 52.2% of DRG neurons and 31.4% of TG neurons in intact animals. These neurons mostly had small-to-medium-sized cell bodies. In the DRG and TG, alpha-2/delta-1 subunit-positive neurons were lightly or moderately st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To determine the proportion of GAL- and CGRP-ir neurons among dura mater neurons, all FG-positive neurons were analyzed in every fifth section of the serial sections of the TG. For cell size analysis of GAL- and CGRP-ir neurons innervating the dura mater, the cross-sectional area of FG-positive cell bodies containing nuclear profiles was measured (Lumina Vision) 54 .…”
Section: Methodsmentioning
confidence: 99%
“…To determine the proportion of GAL- and CGRP-ir neurons among dura mater neurons, all FG-positive neurons were analyzed in every fifth section of the serial sections of the TG. For cell size analysis of GAL- and CGRP-ir neurons innervating the dura mater, the cross-sectional area of FG-positive cell bodies containing nuclear profiles was measured (Lumina Vision) 54 .…”
Section: Methodsmentioning
confidence: 99%
“…It is mainly present in presynaptic terminals and, to a much lower extent, in the cell bodies of neurons in many brain regions under physiological conditions ( Alles and Smith, 2018 ; Bikbaev et al, 2020 ). In the PNS, α2δ1 is strongly expressed in all neuronal cell types of DRG and trigeminal ganglion (TG), such as IB4 + , CGRP + , and NF200 + neurons ( Tachiya et al, 2018 ; Cui et al, 2020 ). It was found that α2δ1 was expressed in most neurons of different sizes after nerve injuries, predominantly in small (less 20 μm) and medium (20–50 μm) neurons in animal models of sciatica neuralgia and trigeminal neuralgia ( Tachiya et al, 2018 ; Cui et al, 2020 ).…”
Section: The α2δ1 Subunit and Its Role In Neuropathic Painmentioning
confidence: 99%
“…In the PNS, α2δ1 is strongly expressed in all neuronal cell types of DRG and trigeminal ganglion (TG), such as IB4 + , CGRP + , and NF200 + neurons ( Tachiya et al, 2018 ; Cui et al, 2020 ). It was found that α2δ1 was expressed in most neurons of different sizes after nerve injuries, predominantly in small (less 20 μm) and medium (20–50 μm) neurons in animal models of sciatica neuralgia and trigeminal neuralgia ( Tachiya et al, 2018 ; Cui et al, 2020 ). In addition, studies using rat models of chronic constriction injury to the infraorbital nerve (CCI-ION) have shown that the number of α2δ1-immunoreactive neurons over 25 μm in diameter was obviously increased ( Li et al, 2014 ).…”
Section: The α2δ1 Subunit and Its Role In Neuropathic Painmentioning
confidence: 99%
“…The schematic drawing shows the central neurite of a primary order dorsal root ganglion neuron and a synapse of such a neuron with a second‐order neuron in the dorsal horn of the spinal cord. The scheme summarises alterations of the voltage‐gated sodium channels (Na V , orange), the adenosine triphosphate (ATP)‐dependent activity of the sodium‐potassium adenosine triphosphatase (Na + /K + ATPase, red), the N ‐methyl‐D‐aspartate receptor (NMDAR, green), the sodium‐potassium‐chloride cotransporter 1 (NKCC1, light blue) the auxiliary voltage‐gated channel subunit α2δ‐1 (purple) and the potassium‐chloride cotransporter 2 (KCC2, dark blue) in the first‐order dorsal root ganglia neurons ( 1 Chang et al., 2017, 2 Sun et al., 2018, 3 Blesneac et al., 2018, 4 Alsaloum et al., 2019, 5 Meents et al., 2019, 6 Qu et al., 2019, 7 Duggett et al., 2017, 8 Yan et al., 2013, 9 McGuinness et al., 2010, 10 Hasbargen et al., 2010, 11 Tan et al., 2020, 12 Luo et al., 2001, 13 Newton et al., 2001, 14 Tachiya et al., 2018, 15 Boroujerdi et al., 2008, 16 Nguyen et al., 2009, 17 Zhou & Luo, 2014).…”
Section: Pathogenic Mechanisms and Recent Findingsmentioning
confidence: 99%
“…The activation allows a calcium influx and thereby promotes the formation of an action potential. Upregulation of the auxiliary subunit α 2 δ‐1 has been found in first‐order neurons of the DRG (Luo et al., 2001; Newton et al., 2001), of the trigeminal ganglion (Tachiya et al., 2018) and of second‐order neurons of the spinal cord's dorsal horn (Boroujerdi et al., 2008) after injury. The altered expression of the subunit is supposed to increase the frequency of the postsynaptic current, recorded in the dorsal horn of the spinal cord (Nguyen et al., 2009; Zhou & Luo, 2014; purple box in Figure 4; the underlying pathway is explained in Section 2).…”
Section: Pathogenic Mechanisms and Recent Findingsmentioning
confidence: 99%